Efficacy of the Novel Degludec/Aspart Insulin Co-formulation in Children and Adolescents with Type 1 Diabetes: A Real-life Experience with One Year of IDegAsp Therapy in Poorly Controlled and Non-compliant Patients - Tarık Kırkgöz; Mehmet Eltan; Sare Betül Kaygusuz; Zehra Yavaş Abalı; Didem Helvacıoğlu; Tuba Seven Menevşe; Büşra Gürpınar Tosun; Tülay Güran; Abdullah Bereket; Serap Demircioğlu (Galenos Yayincilik, 2022)
INTRODUCTION: To evaluate the efficacy of degludec/aspart (IDegAsp) insulin co-formulation in children and adolescents with poorly controlled type 1 diabetes (T1DM). METHODS: Patients with poorly controlled T1DM on basal-bolus insulin regimes and having compliance problems related to insulin injections were switched to IDegAsp and were included. Data on hemoglobin A1c (HbA1c) levels, hypoglycemic episodes, frequency of diabetic ketoacidosis (DKA) and insulin doses were recorded at baseline and after one year of IDegAsp treatment. RESULTS: Fifty patients (22 girls; 44%) were started on IDegAsp. The mean+-standard deviation (range) age and duration of diabetes were 12.9+-3.4 (4-18) and 5.2+-3.1 (1.0-13.7) years, respectively. At the end of one year, 38 patients were still on IDegAsp, whereas 12 patients had opted to resume their original treatments. In those who continued on IDegAsp, HbA1c levels did not change, but the number of self-reported mild-moderate hypoglycemic episodes decreased significantly (p<0.05). In the year before switching to IDegAsp, 11 DKA attacks in 9 patients were observed, whereas this decreased to 4 DKA attacks in 4 patients after one year of IDegAsp therapy (p=0.06). DISCUSSION AND CONCLUSION: IDegAsp regimen may improve clinical management in poorly controlled basal-bolus insulin regimen T1DM patients who have frequent hypoglycemia and DKA attacks, as well as in those with poor compliance with multiple injections. Although a simplified basal-bolus IDegAsp regimen is an attractive option for patients with T1DM, some may not adapt to this treatment due to the fixed IAsp dose of IDegAsp.